Identification of a TLR2 Inhibiting Wheat Hydrolysate. Issue 23 (2nd November 2018) - Kiewiet, Mensiena B. G.; Dekkers, Renske; van Gool, Martine P.; Ulfman, Laurien H.; Groeneveld, Andre; Faas, Marijke M.; de Vos, Paul
Abstract : Scope: Wheat hydrolysates are used in medical nutrition to provide undernourished patients a readily digestible protein source, for instance to recover from chemotherapy‐induced intestinal mucosal inflammation. Since many hydrolysates of different sources can modulate the immune system, likely via Toll‐like receptors (TLRs), it is hypothesized that also wheat hydrolysates might interact with TLR signaling, which could be a way to prevent intestinal inflammation and damage. Methods and results: The capacity of three wheat hydrolysates to modulate immunity by interfering with TLR signaling is determined. All wheat hydrolysates have TLR modulating effects but only one has strong TLR2 inhibiting effects, attenuating both TLR2/1 and TLR2/6 signaling in a reporter cell system. This is likely induced by direct TLR2‐ectodomain binding, as confirmed by ELISA. Furthermore, this TLR2 blocking hydrolysate reduces IL‐6 production in human dendritic cells. Application of reversed‐phase–ultra HPLC combined with MS reveals that the presence of peptide WQIPEQSR is associated with the observed TLR2 inhibiting capacity. Conclusion: The study demonstrates TLR2‐inhibiting capacities of a wheat hydrolysate. The findings provide a good start for further research to investigate whether this hydrolysate might contribute to the management of intestinal mucosal inflammation in cancer patients receiving chemotherapy. Abstract : The capacity of wheat hydrolysates to modulate immunity is determined by interfering with TLR signaling. One wheat hydrolysate has strong TLR2 inhibiting effects in a reporter cell system, likely due to direct TLR2 ectodomain binding, as confirmed by ELISA. On a functional level, the hydrolysate inhibits IL‐6 production in dendritic cells. Furthermore, a peptide in the hydrolysate is found, which is associated with the observed TLR2 inhibiting capacity.